2016
DOI: 10.1163/18773109-00802006
|View full text |Cite
|
Sign up to set email alerts
|

Lying, Uptake, Assertion, and Intent

Abstract: A standard view in social science and philosophy is that a lie is a dishonest assertion: to lie is to assert something that you think is false in order to deceive your audience. We report four behavioral experiments designed to evaluate some aspects of this view. Participants read short scenarios and judged several features of interest, including whether an agent lied. We found evidence that ordinary lie attributions can be influenced by aspects of audience uptake, are based on judging that the agent made an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For this case, the clear majority of participants (96%) evaluated Charlotte's answer as lying but only 35% ascribed an intention to deceive to her (see Krstić, forthcoming, for a critique of indifferent lies). While this case indicates that it is not impossible to construct cases that people consider instances of lying without an intention to deceive, the fact that it happens within a special context—a bet—might also suggests that it is not easy to come up with rather ordinary cases in which lying and an intention to deceive come apart (see Krstić, , Turri & Turri, , for further candidate cases; and Hornung, , for lying with good intentions).…”
Section: Empirical Studies On the Concept Of Lyingmentioning
confidence: 98%
“…For this case, the clear majority of participants (96%) evaluated Charlotte's answer as lying but only 35% ascribed an intention to deceive to her (see Krstić, forthcoming, for a critique of indifferent lies). While this case indicates that it is not impossible to construct cases that people consider instances of lying without an intention to deceive, the fact that it happens within a special context—a bet—might also suggests that it is not easy to come up with rather ordinary cases in which lying and an intention to deceive come apart (see Krstić, , Turri & Turri, , for further candidate cases; and Hornung, , for lying with good intentions).…”
Section: Empirical Studies On the Concept Of Lyingmentioning
confidence: 98%
“…Closely related to assertions, lies which are regarded as dishonest assertions have also gained much attention in experimental philosophy of language in recent years. Turri and Turri (2016) assessed the common view that to tell a lie is to make false assertion in order to deceive others in a series of behavioral experiments. What they found is that attributions of lies are subjected to the influence of audience uptake and are based on attributions of assertion rather than attribution of deceptive intentions.…”
Section: Major Research Themesmentioning
confidence: 99%
“…One study found that lie attributions are affected by the audience's ability to hear an agent's spoken words, and that this effect was mediated by judgments about whether the agent made an assertion (Turri and Turri 2016, experiment 1). A second study found that lie attributions and assertion attributions were significantly correlated (Turri and Turri 2016, experiment 2).…”
mentioning
confidence: 91%